2015
DOI: 10.3892/mmr.2015.4233
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin inhibits the proliferation of adenoid cystic carcinoma via suppression of glucose transporter-1

Abstract: Apigenin is a natural phyto-oestrogen flavonoid, which exerts various biological effects, including anti-oxidative, anti-inflammatory and anticancer activities. In addition, apigenin has recently been reported to target hypoxic markers; however, there are currently no studies regarding the association between apigenin and glucose transporter-1 (GLUT-1) in adenoid cystic carcinoma (ACC). The present study investigated whether apigenin inhibits the proliferation of ACC cells or suppresses the expression of GLUT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…It was previously demonstrated that APG caused arrest of the cell cycle in G 0 /G 1 -phase by reducing the level of cyclin D1 in LNCaP and PC-3 prostate cancer cell lines (1). However, in other studies, APG caused cell-cycle arrest at the G 2 -phase by decreasing cyclin B in human colon carcinoma and pancreatic cancer cells (10), or regulated other cell-cycle phases by affecting cyclin A and cell division cycle 25A and cell division cycle 25C in different cell types (8,(69)(70)(71). The results of the cell-cycle assay of the present study suggested that APG arrested Rad54 -/cells in G 2 /M-phase.…”
Section: Discussioncontrasting
confidence: 55%
“…It was previously demonstrated that APG caused arrest of the cell cycle in G 0 /G 1 -phase by reducing the level of cyclin D1 in LNCaP and PC-3 prostate cancer cell lines (1). However, in other studies, APG caused cell-cycle arrest at the G 2 -phase by decreasing cyclin B in human colon carcinoma and pancreatic cancer cells (10), or regulated other cell-cycle phases by affecting cyclin A and cell division cycle 25A and cell division cycle 25C in different cell types (8,(69)(70)(71). The results of the cell-cycle assay of the present study suggested that APG arrested Rad54 -/cells in G 2 /M-phase.…”
Section: Discussioncontrasting
confidence: 55%
“…Mori et al detected higher expression of GLUT-1 mRNA in ACC than in normal salivary glands by RT-PCR [60]. In our previous study, GLUT-1 mRNA and protein showed high expression in ACC-2 cell lines [63]. Demasi et al found higher expression of GLUT-1 in high-grade MEC than in low-grade MEC of the salivary gland as detected by IHC.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, in renal cell carcinoma cells, apigenin caused DNA damage in ACHN cells in a time- and dose-dependent manner and induced G2/M phase cell cycle arrest through ataxia telangiectasia mutated (ATM) signal modulation [ 30 ]. In adenoid cystic carcinoma (ACC), apigenin induced G2/M-phase arrest and inhibited ACC-2 cell growth and proliferation in a dose- and time-dependent manner by decreasing the expression of Glucose transporter-1 (GLUT-1) [ 31 ]. And in human papillary thyroid carcinoma BCPAP cells, apigenin treatment caused G2/M cell cycle arrest via down-regulation of Cdc25c expression and stimulated the accumulation of reactive oxygen species (ROS) production, leading to induction of DNA damage [ 32 ].…”
Section: Apigenin In Cancer Therapymentioning
confidence: 99%